Welfare reform, saving, and vehicle ownership: Do asset limits and vehicle exemptions matter? - James X. Sullivan (W.E. Upjohn Institute for Employment Research, 2005)
This paper examines whether AFDC/TANF asset tests affect the asset holdings of low-educated single mothers. Special emphasis is given to vehicle assets that make up a very significant share of total wealth for poor families. Consistent with other recent research, I find little evidence that asset limits have an effect on the amount of liquid assets that single mothers hold. However, I find evidence that vehicle exemptions do have an important effect on vehicle assets. Also, the results indicate that single mothers are not substituting vehicle equity for liquid assets in response to more relaxed restrictions on vehicles.
Keywords: 330; Sozialhilfe; Reform; Alleinerziehende; Sparen; USA